Developmental adaptation of central nervous system to extremely high acetylcholine levels - Farar, Vladimir; Hrabovska, Anna; Krejci, Eric; Myslivecek, Jaromir (PloS one, 2013)
Acetylcholinesterase (AChE) is a key enzyme in termination of fast cholinergic transmission. In brain, acetylcholine (ACh) is produced by cholinergic neurons and released in extracellular space where it is cleaved by AChE anchored by protein PRiMA. Recently, we showed that the lack of AChE in brain of PRiMA knock-out (KO) mouse increased ACh levels 200-300 times. The PRiMA KO mice adapt nearly completely by the reduction of muscarinic receptor (MR) density. Here we investigated changes in MR density, AChE, butyrylcholinesterase (BChE) activity in brain in order to determine developmental period responsible for such adaptation. Brains were studied at embryonal day 18.5 and postnatal days (pd) 0, 9, 30, 120, and 425. We found that the AChE activity in PRiMA KO mice remained very low at all studied ages while in wild type (WT) mice it gradually increased till pd120. BChE activity in WT mice gradually decreased until pd9 and then increased by pd120, it continually decreased in KO mice till pd30 and remained unchanged thereafter. MR number increased in WT mice till pd120 and then became stable. Similarly, MR increased in PRiMA KO mice till pd30 and then remained stable, but the maximal level reached is approximately 50% of WT mice. Therefore, we provide the evidence that adaptive changes in MR happen up to pd30. This is new phenomenon that could contribute to the explanation of survival and nearly unchanged phenotype of PRiMA KO mice.
Keywords: acetylcholinesterasa; myši; signální transdukce; Nerve Tissue Proteins; Protein Binding; Butyrylcholinesterase; Mice, Knockout; Male; myši knockoutované; novorozená zvířata; Brain; Signal Transduction; Receptors, Muscarinic; Cholinergic Neurons; Gene Expression Regulation, Developmental; receptory muskarinové; Adaptation, Physiological; Acetylcholine; Mice; Animals; Animals, Newborn; zvířata; vazba proteinů; butyrylcholinesterasa; proteiny nervové tkáně; mužské pohlaví; mozek; fyziologická adaptace; Embryo, Mammalian; Membrane Proteins; membránové proteiny; neurony cholinergní; embryo savčí; Acetylcholinesterase; acetylcholin; vývojová regulace genové exprese